2009
DOI: 10.1177/0003319709344576
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Disease and Sjögren Syndrome: A Possible Correlation?

Abstract: This study shows that capillary alterations to patients with SS occur in gingival microcirculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 28 publications
1
20
0
1
Order By: Relevance
“…Serum antibody levels to periodontopathogens were significantly higher in Sjögren syndrome patients than in control subjects (25). A case-control study suggested a possible correlation between periodontal disease and Sjögren syndrome, as capillary alterations in gingival microcirculation were observed in patients with Sjögren syndrome (27). Plaque accumulation associated with low salivary flow rate might affect gingival inflammation and blood circulation.…”
Section: Discussionmentioning
confidence: 96%
“…Serum antibody levels to periodontopathogens were significantly higher in Sjögren syndrome patients than in control subjects (25). A case-control study suggested a possible correlation between periodontal disease and Sjögren syndrome, as capillary alterations in gingival microcirculation were observed in patients with Sjögren syndrome (27). Plaque accumulation associated with low salivary flow rate might affect gingival inflammation and blood circulation.…”
Section: Discussionmentioning
confidence: 96%
“…Sjögren syndrome seemed to negatively affect the periodontal condition because gingival inflammation is more evident in the individuals with Sjögren syndrome particularly those with secondary Sjögren syndrome [21]. According to Scardina, periodontal disease can be caused by capillary alterations especially in gingival microcirculation [22]. A likely effect of anti-inflammatory, immunosuppressive and glucocorticoid drugs on an inflammatory response of periodontal tissues must also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Geographical region was selected because the prevalence of some environmental risk factors for RA may differ among regions. SS was selected because it was found to increase wrist and periodontal bone destruction risk in patients with RA,35 and may be associated with periodontitis 36. In Taiwan, the classification criteria proposed in 1986 and the revised classification criteria by the American–European Consensus Group in 2002 were used as criteria for certifying SS as a catastrophic illness before and after 2002, respectively 37.…”
Section: Methodsmentioning
confidence: 99%